More stories from Langley : another glimpse inside the CIA - Mickolus, Edward F. (Potomac Books, An imprint of the University of Nebraska Press, 2020)
"Collection of personal essays detailing the adventures, advice, and experience of generations of CIA support and technical officers"-- Provided by publisher
Keywords: United States. -- Central Intelligence Agency -- Officials and employees -- Biography -- Anecdotes. 610.; United States. -- Central Intelligence Agency -- History -- Anecdotes.; United States. -- Central Intelligence Agency; Intelligence officers -- United States -- Biography -- Anecdotes.; Spies -- United States -- Biography -- Anecdotes.; Intelligence service -- United States -- Anecdotes.; Officiers de renseignements -- États-Unis -- Biographies -- Anecdotes.; Employees; Intelligence officers; Intelligence service; Spies; United States; Anecdotes; Biographies; History